Demographic, Comorbidity, and Episode-of-Care Differences in Primary Total Knee Arthroplasty. (3rd February 2021) - Siddiqi, Ahmed; Warren, Jared A.; McLaughlin, John; Kamath, Atul F.; Krebs, Viktor E.; Molloy, Robert M.; Piuzzi, Nicolas S.
Abstract : Background: Understanding time trends in age, demographic characteristics, and comorbidities is especially critical to highlight the effects on clinical practice change, outcomes, and the value of total knee arthroplasty (TKA). Therefore, the purpose of this study was to identify trends in the demographic characteristics, comorbidities, and episode-of-care outcomes for patients who underwent TKA from 2008 to 2018. Methods: The National Surgical Quality Improvement Program (NSQIP) was queried to identify patient demographic characteristics, comorbidities, and episode-of-care outcomes in patients who underwent primary TKA from 2008 to 2018 (n = 350, 879). Trends for continuous variables were analyzed using analysis of variance, and categorical variables were analyzed using chi-square tests. Results: From 2008 to 2018, there was no clinically important difference in age, body mass index (BMI), and percentage of patients with BMI of >40 kg/m2 and no clinically important difference in chronic obstructive pulmonary disease (3.5% in 2008 and 3.2% in 2018), congestive heart failure within 30 days (0.3% in both 2008 and 2018), and acute renal failure (0.1% in 2008 and <0.1% in 2018) among patients undergoing TKA. However, modifiable comorbidities, including smoking status (9.5% in 2008 and 7.7% in 2018; p < 0.001), hypertension (71.0% in 2008 and 63.7% in 2018; p < 0.001), and anemia (16.2% in 2008 and 9.7% in 2018; p < 0.001), functional status, and overall morbidity and mortality probability have improved, with no clinically important difference in the percentage of diabetes (19.0% in 2008 and 18.1% in 2018). The hospital length of stay (mean [and standard deviation], 3.8 ± 2.2 days in 2008 and 2.1 ± 2.0 days in 2018; p < 0.001) and 30-day readmission (4.6% in 2011 and 3.0% in 2018; p < 0.001) decreased, with a significant increase in home discharge (65.6% in 2011 and 87.8% in 2018; p < 0.001). Conclusions: The overall patient health status improved from 2008 to 2018, with improvement in the modifiable comorbidities of smoking status, malnutrition, hypertension, and anemia; the functional status; and the overall morbidity and mortality probability, with no clinically relevant change in patient age; patient BMI; percentage of patients with BMI of >40 kg/m2; or patients with diabetes mellitus, chronic obstructive pulmonary disease, congestive heart failure within 30 days, or acute renal failure. Our findings may be a reflection of a global shift toward value-based care focusing on patient optimization prior to arthroplasty, quality of care, and improved outcomes. The results of our study highlight the potential increase in TKA procedural value, which is paramount for health-care policy changes in today's incentivized, value-based, health-care environment.